Understanding the Dynamics of Unemployment and Poverty in the Tomini Bay Area - Dai, Sri Indriyani S.; Hasan, Sherina; Setiawan, Widy (EcceS: Economics, Social, and Development Studies, 2023)
This study aims to analyze the effect of education level, gini ratio and labor force participation rate on unemployment, as well as the effect of unemployment on poverty in the Tomini Bay region. The data used in the study is secondary data in the form of 10 regencies/cities in the Tomini Bay area, for the 2018-2022 period, sourced from the Indonesian Central Bureau of Statistics. The novelty of this study is trying to trace the relationship between educational and economic aspects to the phenomenon of poverty in the Tomini Bay Region, as a regional economic power. The future impact of this study is the mapping of the actual condition of poverty and the availability of more evidence-based policy recommendations in reducing unemployment and poverty in the Tomini Bay Area. This study used descriptive quantitative methods. With an approach (Simultaneous equation regression model) using the Indirect Least Square (ILS) regression technique with Fixed Effect Model (FEM). The results of this study show that the level of education and the labor force participation rate have a negative and significant effect on unemployment. In contrast to the Gini ratio which actually has a positive and significant effect on unemployment. On the other hand, unemployment shows a positive and significant influence on poverty. The implication of the research is the need for a truly massive policy to strengthen the education dimension, to accelerate the increase in human capital and the importance of a sustainable program to increase employment opportunities from the government so as to reduce unemployment and poverty.